Efektivitas Penerapan Media Permainan Spelling Bee Untuk Meningkatkan Penguasaan Kosakata Bahasa Arab - Novi Ilmi Anggraini; Khairy Abusyairi; Muhammad Ihsanuddin Masdar (El-Syaker : Samarinda International Journal of Language Studies, 2024)
Interactive and competitive learning media, such as Spelling Bee, have the potential to increase students' involvement in the learning process, which can have a positive impact on their learning outcomes, this study aims to examine the effectiveness of spelling bee learning media in improving the mastery of Arabic vocabulary of MIN 2 Samarinda students. This research is a quantitative study using a quasi-experimental approach, with a sample of 68 people consisting of 34 people (experimental class) and 34 people (control class). The data collection methods used were observation, interviews, tests consisting of pre-test and post-test and documentation. The data analysis techniques used were descriptive analysis test, normality test, homogeneity test, independent sample t-test, and N-Gain test. The results showed that the experimental group using spelling bee learning media experienced a significant increase in vocabulary mastery compared to the control group using conventional learning methods. The post-test mean value of the experimental group was 80.88, while the control group achieved a post-test mean value of 61.03 In addition, the Sig value of the t-test results of the significance value (Sig. (2 tailed)) of 0.00 because the Sig value <0.005, as the independent sample t-test test decision making that H0 is rejected and H1 is accepted. Thus, the researcher concluded that spelling bee learning media is effective in learning Arabic vocabulary.